Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1021/ja00220a085
|View full text |Cite
|
Sign up to set email alerts
|

Triticones A and B, novel phytotoxins from the plant pathogenic fungus Drechslera tritici-repentis

Abstract: Table I. Secondary Tritium Isotope Effects in E2 Reactions of ArCLTCH2X and ArCL2CH2X (L = H or D) at 50 OC reaction kHlkT k d k T ( k~l k~L i c d ' 1" + EtONafEtOH 1.204 f 0.015 1.0314 f 0.010 1.106 f 0.033 2b + t-BuOKfr-BuOH 1.191 f 0.012 1.0274 f 0.008 1.092 f 0.026 a 2-Phenylethyltrimethylammonium bromide. 2-@-Chlorophenyl)ethyl tosylate. cFrom the relation k H / k T = (kD/kT)3,z6 (ref 8 and 9).transferred hydrogen are coupled with the stretching motion of the transferred hydrogen. The calculations also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 2 publications
2
47
0
Order By: Relevance
“…This conjugation would also account for the shielding of C 3 and the deshielding of C2 relative to the positions of the corresponding propenyl sp2 carbon signals in the spectrum of ( E ) -propeny lbenzene. Acetylation of cycloarthropsone (12) (12). These shifts are in accordance with those expected from a comparison of the spectra of phenol and phenyl acetate (7).…”
Section: Arthropsadiol B (3)supporting
confidence: 85%
See 2 more Smart Citations
“…This conjugation would also account for the shielding of C 3 and the deshielding of C2 relative to the positions of the corresponding propenyl sp2 carbon signals in the spectrum of ( E ) -propeny lbenzene. Acetylation of cycloarthropsone (12) (12). These shifts are in accordance with those expected from a comparison of the spectra of phenol and phenyl acetate (7).…”
Section: Arthropsadiol B (3)supporting
confidence: 85%
“…The I3c nlnr spectrum of arthropsolides B (25) Arthropsolide B (25) and C (26) are very similar in terms of structure and instability to the inseparable mixtures of spirostaphylotrichin G (27) and H (28) from Staphylotrichum coccosporum (lo), and triticone A (23) and B (24) from Staplzyloticlzum coccosporum (9) and Drechsleln tritici-repentis (12). Drechslera ti-itici-repentis is a major pathogen of wheat and it has been suggested that the retro-aldol intermediate 29 by which triticone A and B readily interconvert may be responsible for the lesions produced on wheat plants by this fungus (12).…”
Section: And C (26)mentioning
confidence: 99%
See 1 more Smart Citation
“…Three host specific toxins, the proteinaceous effectors ToxA and ToxB and the semi‐characterized small molecule effector ToxC have been described for Ptr (Effertz et al ., ; Ciuffetti et al ., ; Lamari and Strelkov, ). In addition, two classes of specialized metabolites, anthraquinones and triticones, have been reported as non‐specific phytotoxins (Sugawara et al ., ; Hallock et al ., ; Kachlicki and Wakulinski, ; Bouras and Strelkov, ). Anthraquinones are characterized by three fused aromatic rings and harbour a variety of substituents.…”
Section: Introductionmentioning
confidence: 98%
“…Triticones A to F were first purified from Ptr culture filtrates but have since been found, along with an additional 18 other triticone compounds, in 5 other ascomycete fungi, Staphylotrichum coccosporum , Curvularia pallescens , Pyrenophora seminiperda , Cochliobolus lunatus and Bipolaris spp. (Sugawara et al ., ; Sandmeier and Tamm, ,b, ; Hallock et al ., ; Abraham et al ., ; de Almeida et al ., ; Wang et al ., ). Triticone A and B are known to be phytotoxic, producing yellowish‐brown lesions following leaf puncture assays on a range of hosts including wheat.…”
Section: Introductionmentioning
confidence: 98%